The investigation of physical dan mechanical properties of Nipah-based particle board - Hendri Nurdin; Waskito Waskito; Anna Niska Fauza; Batu Mahadi Siregar; Bagdaulet Kenzhaliyevich Kenzhaliyev (Teknomekanik, 2023)
The excessive use of wood as a raw material in furniture industries has raised environmental concerns that have attracted the attention of many individuals. Consequently, various innovations have been explored in developing alternative materials for the furniture industry. One promising resource that has the potential to be developed as a raw material for furniture applications is Nipah palm husk. Nipah palm husk is classified as an agricultural waste that is barely used within society and industries. Hence, in this study, Nipah palm husk will be utilized as the primary material to fabricate particle board by involving tapioca as an adhesive. This research aimed to investigate the effect of tapioca concentrations on water absorption, modulus elasticity, modulus of rupture, and screw-holding strength of the produced Nipah palm husk particleboard. The results of this study showed that the particle board produced with a 40% tapioca adhesive concentration exhibited the most favorable physical and mechanical properties with a water absorption rate of 25%, an elastic modulus of 21188.93 kg/cm2, a modulus of rupture of 55.53 kg/cm2, and a screw holding power of 7.53 kg. The findings indicated that Nipah-based particle board has the potential to be developed as an alternative for the furniture industry.